CRITICAL ANALYSIS OF PROJECT MANAGEMENT IN A DEVELOPING COUNTRY - THE CASE OF THE GAMBIA - WADDA, AMADOU TEJAN (2005)
A good well maintained infrastructure network is the cornerstone of a country's economic development. It is in recognition of this fact that many Sub-Sahara Africa (SSA) countries (including the Gambia), have in recent years been investing massively in infrastructure projects. Many of these projects have however not achieved their originally stated goals of timely completion, within budget, and full compliance with the required specifications.